Uncertainties evaluation and analysis using quantitative technique for a software project. (19th November 2021) - Singh, Harvinder; Kumar, Adarsh; Ravulakollu, Kiran Kumar; Kumar, Manoj; Stephan, Thompson
Opportunities cannot be converted into achievements without assessing risk. Software developers and project managers presume that activities would proceed smoothly and according to plan in software project development. However, in reality, this is not always true due to the existence of unseen risks that influence the development process and thereby performance. Hence, there is a need for more realistic risk evaluation criteria that can address the project managers need. This paper proposes a project risk evaluation technique (PRET) to determine the attractiveness of a software project. The proposed technique used normal distribution ( DN ) approach for risk understanding and thereby use the activity network to assess them. Using the graph theory method, with nodes as phases of the development process and edges as the duration of phases and the whole network as a software project, the algorithm systematically represented to extend various influential aspects of risk analysis. Hence, using quantitative analysis, the proposed algorithm is evaluated against negative exponential distribution ( DNE ) and is found to have a slight degree of uncertainty associated with risk and attractiveness. This signifies that there is still a scope of improvement for stabilising the proposed technique with minimal improvements in the project factors.